Techniques to infer admixture using genome-wide autosomal DNA 2 - Hellenthal, Garrett (Henry Stewart Talks, 2022)
Haplotype-based GLOBETROTTER admixture detection and dating software, Haplotype-based MOSAIC admixture detection, dating, and local-ancestry-inference software, Limitations of admixture dating methods